Determining the temporal limits of a visual sample for visual regulation - Hansen, S. (Journal of Motor Behavior, 2010)
The author examined the minimum amount of time needed for vision to increase aiming accuracy and decrease movement duration. Participants selected when they would receive a visual sample during aiming movements by pressing a switch held with the left hand. The sample was one of the following durations: 40 ms, 30 ms, 20 ms, 10 ms, or 0 ms (no vision). Decreased accuracy in the no-vision condition compared to the vision conditions was observed when the duration of the impending sample was unknown (Experiment 1). Samples 40 ms in duration were sufficient to decrease endpoint variability when the duration of the sample was known before the movement (Experiment 2). These results indicate that short visual samples can be used to decrease movement time and increase accuracy and that knowledge of the impending visual context can impact the individual's subsequent behavior